Management of Zakat Funds in Zakat Management Institutions - Rahman, Nailur; Eletmany, Mohamed R.; Asyaari, Asyaari; Jalaluddin, Moh.; Muammar, Muammar (Al Irsyad: Jurnal Studi Islam, 2024)
The lack of integration between traditional zakat management methods at BAZNAS and LAZ with modern technology hinders efficiency. At the same time, the Sidogiri Amil Zakat Institution offers an innovative approach as a socio-economic force for the community. This study aims to explore and understand the implementation of zakat fund management at the Sidogiri Amil Zakat Institution. Using a qualitative approach and ethnographic methods, data were collected through interviews, observations, and documentation. Data processing was carried out through condensation, presentation, and drawing conclusions, with data validity maintained through triangulation of techniques and sources. The research findings reveal several key results: 1) Zakat collection is actively conducted in various locations such as cities, districts, villages, residential areas, companies, shops, mosques, and through visits to communities and local leaders by collection officers. 2) Zakat funds are distributed in the form of zakat fitrah, money, staple needs such as rice, as well as assistance for orphans, scholarships, construction of worship facilities, and provision of clean water, in accordance with the principle of the eight eligible recipients. 3) Funded programs include assistance for underprivileged elderly individuals, while other programs, such as education, preaching, health, economy, humanitarian aid, and environmental efforts, do not utilize zakat funds. Conclusion: LAZ Sidogiri effectively manages the collection and distribution of zakat through various programs that help the recipients, support education, health, and economic initiatives to improve welfare and empower the community sustainably.